REALITY - REALIZATION THROUGH SELF-DISCIPLINE - Vempeny, Alice (Journal of Dharma, 1989)
Yoga philosophy as systamatised by Patanjali is typically Indian in its analysis. It upholds the best Indian values and concepts of life and liberation. Yet it has a definite message for peoples of all cultures, religions and social groups. It speaks to the person as person, not specifically as European or Indian. Though deeply linked to the Indian style of living and Indian ways of thinking, it still can be expressed in different cultural backgrounds and be made relevant to any human situation.